Spesolimab in generalized pustular psoriasis complicated by acrodermatitis continua of Hallopeau: a case report and mechanistic insights - Hou, Xin-Yi; Xiao, Hai-Lu; Wang, Jing-Yu; Zhang, Jin; Ren, Bo; Niu, Chu-chu; Liu, Fei-Fei; Lu, Bin (Frontiers in Immunology, 2025)
A 62-year-old Chinese woman presented to the hospital for help with generalized pustular psoriasis (GPP) and acrodermatitis continua of Hallopeau (ACH). While conventional treatments failed to achieve significant improvement, the patient received two doses of spesolimab, and the effect was remarkable. No adverse reactions were observed in the follow-up period.